Adaptive Learning Media in Implementation of Islamic Religious Education of Autistic Children at SLB Negeri 2 Katingan Hilir Regency - Almajidah, Almajidah; Normuslim, Normuslim; Wahdah, Nurul (CV. Creative Tugu Pena, 2021)
The article was to analyze adaptive learning media in the implementation of Islamic religious education in children autism at special education schools, special education schools for students with special needs, where students have different characteristics either physically or mentally. This research was descriptive qualitative study with the type of field research. 20 participants were selected in this research. Data collection used observation, inteviews and documentation. Interview was conducted by the 20 teachers. Data analysis used interactive model by Miles and Huberman. There were three steps in this model, namely data reduction, data display and conclusion/verification. The result showed that the different needs and characteristics of children required the use of appropriate learning media in the implementation of Islamic religious education, namely adaptive learning media that adjusted to the needs and characteristics of children with autism. Before determining the learning media, an assessment was first carried out hence it makes it easier for the teacher to determine the learning media that suits the needs and caracteristics of the children. In using adaptive media, it was focused on self care practice, receptive language skills and expressive language using the media in the form of hijaiyah letter cards, short chorded surah word card and pictures. Keywords: Adaptive Learning Media, Islamic Religious Education, Autistic Children Learning